Fatty Acids, Volatile and Sensory Profile of Multigrain Biscuits Enriched with Spent Malt Rootles - Chiş, Maria Simona (Molecules, 2020)
Spent malt rootlets, a by-product of the brewing industry, are a rich source of protein, essential amino acids, healthy fats, polyphenols and minerals, and could be a new promising type of raw material from the nutritional, economic, sensory, and technical perspectives. However, their specific aroma profile could limit their addition in baked products. The aim of this work was to study the effect of spent malt rootlets addition on volatile derivatives of enriched biscuits in relation to their sensory profile. For this purpose, spent malt rootlets and enriched biscuits (0–25% spent malt rootlets added) were analyzed by GC-MS techniques, in order to obtain their fatty acids methyl esters and volatile compounds profile, while for the sensory analysis a nine-point hedonic score test was used. The results of this study reveal the fatty acids and volatile profile of spent malt rootlets and of the enriched biscuits with spent malt rootlets pointing out the contribution of fatty acids to the generation of aroma compounds. The influence of different aroma compounds on the consumer’s preferences was studied and the optimum level addition of spent malt rootlets in multigrain biscuits was found to be 15%.